Lessons Learnt from the Monetary System of Guernsey - Gábor Sárdi; József Varga (DETUROPE)
Bailiwick of Guernsey, situated in the English Channel off the coast of Normandy, just like Jersey and the Isle of Man, is an UK Crown dependency and an autonomous jurisdiction. These Crown dependencies are not members of the Commonwealth of Nations nor of the European Union. Furthermore, Guernsey is not part of France nor of the United Kingdom. This atypical status of Guernsey runs back several hundred years: from 1204 the island takes advantage of its special legal status and in general, it has not been managed badly. Despite all this, it cannot be considered as a totally independent, sovereign state. In addition to its special legal status, Guernsey is considered to be special in regard to its money system. According to a very popular story spread across the economic literature, the issuance of Guernsey pound prospered the island as some kind of a magic cure. While it is a considerable part, the current paper emphasize that it was not the only factor. The issuance happened in an economically declining period of Guernsey: after the Napoleonic wars the previous successful economic situation became worse mainly because of the actions of the British authorities that suppressed smuggling, a formerly thriving economic sector of the island. People established their living on this activity were hit hard, but as before, looked for opportunities where their unique status could be used efficiently, and thus, could stabilize their conditions (shipbuilding, vegetable production, tourism, etc.). Guernsey’s money system, however, remains an important topic as its way of operation is indeed unusual in the global economy. Whereas money supply in most countries consists primarily of privately issued bank-debt money (about 95%), Guernsey (States of Guernsey) finance its public spending via quasi state issued money since 1817. This type of money system is usually termed as ‘public money system’ and receives a growing attention nowadays.